A distance-triggered signaling on–off mechanism by plasmonic Au nanoparticles: toward advanced photocathodic DNA bioanalysis. Issue 9 (6th January 2020) - Fan, Gao-Chao; Zhao, Huan; Ma, Linzheng; Lu, Yanwei; Luo, Xiliang
Abstract : An advanced signaling on–off mechanism was first proposed by integrating exciton–plasmon coupling and exciton energy transfer into cathodic PEC bioassays for ultrasensitive and specific detection of tDNA. Abstract : An efficient signaling on–off mechanism was first proposed by integrating exciton–plasmon coupling and exciton energy transfer into cathodic PEC bioassays. This signaling on–off mechanism has endowed the cathodic PEC biosensor with powerful capability for ultrasensitive and specific detection of target DNA.